The Struggles to Overcome Traumatic Deviant Sexual Abuses as Starkly Portrayed in “Funeral Rites” by Jack Dickson - Ratna Asmarani; Inni Inayati Istiana; Tri Wahyuni (SAWERIGADING, 2024)
The short story titled "Funeral Rites" is about deviant sexual activity in the form of forced incest in several underage victims. This study analyzed the deviant forms of sexual abuse, devastating trauma, and unique solutions for letting go of the trauma. This study uses Sigmund Frued’s theory of literary and psychosexual psychology. The research method used is qualitative, and the results are descriptive. The concepts used to support the analysis are the definitions of incest, pedophilia, bisexuality, homosexuality, and other related issues. The results show that there were sexual deviations, such as incest-pedophilia-heterosexual rapes and incest-pedophilia-homosexual rapes performed repeatedly by the same predator, the older person, who should protect and care for young victims. Leave devastating and haunting trauma to the under-age victim. The eldest victim finally finds a unique solution to reduce the traumatic effects that they have endured for years.  AbstrakCerpen berjudul "Funeral Rites" ini bercerita tentang aktivitas seksual menyimpang berupa inses paksa pada beberapa korban di bawah umur. Penelitian ini menganalisis bentuk-bentuk menyimpang dari pelecehan seksual, trauma yang menghancurkan, dan solusi unik untuk melepaskan trauma. Penelitian ini menggunakan teori sastra dan psikologi psikoseksual Sigmund Frued. Metode penelitian yang digunakan adalah deskriptif-kualitatif. Konsep yang digunakan untuk mendukung analisis adalah definisi inses, pedofilia, biseksualitas, homoseksualitas, dan isu-isu terkait lainnya. Hasil penelitian menunjukkan bahwa ada penyimpangan seksual, seperti pemerkosaan inses-pedofilia-heteroseksual dan pemerkosaan inses-pedofilia-homoseksual yang dilakukan berulang kali oleh predator yang sama, orang tua yang seharusnya melindungi dan merawat korban muda. Korban tertua akhirnya menemukan solusi unik untuk mengurangi efek traumatis yang telah mereka alami selama bertahun-tahun.